miR-181a Induces Macrophage Polarized to M2 Phenotype and Promotes M2 Macrophage-mediated Tumor Cell Metastasis by Targeting KLF6 and C/EBPα - Jia Bi; Xianxin Zeng; Lin Zhao; Qian Wei; Lifeng Yu; Xinnan Wang; Zhaojin Yu; Yaming Cao; Fengping Shan; Minjie Wei (Elsevier, 2016)
Macrophages can acquire a variety of polarization status and functions: classically activated macrophages (M1 macrophages); alternatively activated macrophages (M2 macrophages). However, the molecular basis of the process is still unclear. Here, this study addresses that microRNA-181a (miR-181a) is a key molecule controlling macrophage polarization. We found that miR-181a is overexpressed in M2 macrophages than in M1 macrophages. miR-181a expression was decreased when M2 phenotype converted to M1, whereas it increased when M1 phenotype converted to M2. Overexpression of miR-181a in M1 macrophages diminished M1 phenotype expression while promoting polarization to the M2 phenotype. In contrast, knockdown of miR-181a in M2 macrophages promoted M1 polarization and diminished M2 phenotype expression. Mechanistically, Bioinformatic analysis revealed that Kruppel-like factor 6 (KLF6) and CCAAT/enhancer binding protein-α (C/EBPα) is a potential target of miR-181a and luciferase assay confirmed that KLF6 and C/EBPα translation is suppressed by miR-181a through interaction with the 3'UTR of KLF6 and C/EBPα mRNA. Further analysis showed that induction of miR-181a suppressed KLF6 and C/EBPα protein expression. Importantly, miR-181a also diminishes M2 macrophages-mediated migration and invasion capacity of tumor cells. Collectively, our results suggest that miR-181a plays a significant role in regulating macrophage polarization through directly target KLF6 and C/EBPα.